2003
DOI: 10.1038/sj.mp.4001440
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of the dopamine receptor D1 gene to attention-deficit/hyperactivity disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) has a strong genetic basis, and evidence from human and animal studies suggests the dopamine receptor D1 gene, DRD1, to be a good candidate for involvement. Here, we tested for linkage of DRD1 to ADHD by examining the inheritance of four biallelic DRD1 polymorphisms [D1P.5 (-1251HaeIII), D1P.6 (À800HaeIII), D1.1 (À48DdeI) and D1.7 ( þ 1403Bsp1286I)] in a sample of 156 ADHD families. Owing to linkage disequilibrium between alleles at the four markers, only three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 69 publications
4
65
2
1
Order By: Relevance
“…Gα olf is a key effector molecule in signalling of the D1 receptor, for which evidence of association has been reported for ADHD (Bobb et al, 2005;Misener et al, 2004), particularly with the inattention symptoms in children with ADHD (Misener et al, 2004) or reading difficulties (Luca et al submitted for publication). Most association studies have focused on neurotransmitter receptor or transporter level, however, G proteins are central in the regulation of different pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gα olf is a key effector molecule in signalling of the D1 receptor, for which evidence of association has been reported for ADHD (Bobb et al, 2005;Misener et al, 2004), particularly with the inattention symptoms in children with ADHD (Misener et al, 2004) or reading difficulties (Luca et al submitted for publication). Most association studies have focused on neurotransmitter receptor or transporter level, however, G proteins are central in the regulation of different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the association between the dopamine receptor D1 gene (DRD1) and ADHD (Misener et al, 2004), particularly between one haplotype and inattention symptoms (P = 0.008). Recently, we replicated the association between this haplotype and inattentive behaviors in children selected for reading difficulties (P = 0.004) (Luca et al, submitted for publication).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary evidence suggests aetiological influences of the receptor genes DRD1 [101] and 5-HT(1B) [66,118], the Taq 1 polymorphism of the dopamine beta hydroxylase gene [31,148], and the SNAP-25 gene, which is involved in the regulation of neurotransmitter release [12,100].…”
Section: Influences On Pathogenesismentioning
confidence: 99%
“…11 Further support for an association of the DRD1 gene has been reported by Bobb et al 12 in a case-control study. They found a significantly higher frequency of the rs4532C and rs265981A marker alleles, which are also included in Misener et al's overtransmitted haplotype.…”
mentioning
confidence: 67%
“…11 In addition, another study has suggested that the 148 bp allele of a microsatellite marker located 18.5 kb from the DRD5 gene may be associated primarily with the inattentive and combined subtypes (rather than the hyperactive/impulsive subtype) of ADHD. 10 Thus, it seems that the influence of the DRD1, DRD5 and calcyon genes on the expression of ADHD symptoms does not overlap completely, although we acknowledge that replication studies are still needed for the DRD1 and calcyon genes, and that quantitative analysis of the 148 bp variant of DRD5 may give more definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%